Environmental Impact Assessment a Key to Sustainable Development (West African Journal on Sustainable Development, 2024)
Environmental protection is the primary concern of the future of humanity. It defines how to protect ecosystems, air quality, integrity, and sustainability of our resources and focuses on the elements that place stress on the environment. environmental impact assessment (EIA) is a pivotal tool for sustainable development. EIA helps identify impacts, engage stakeholders, and modify proposals to protect ecosystems. Environmental impact assessment (EIA) is a vital process that offers a range of advantages, contributing to responsible and sustainable development. EIA is a forward-looking tool that systematically assesses proposed projects and developments. By doing so, it identifies potential environmental impacts before they occur. EIA is aligned with the principles of sustainable development . It ensures that projects are not just economically viable but also environmentally and socially responsible. EIA is instrumental in safeguarding our planet’s natural resources and ecosystems. By evaluating the potential impacts of development projects, EIA can identify areas of high ecological importance. EIA is a transparent process that encourages stakeholder and public engagement . By involving various parties, from local communities to environmental organizations, EIA ensures that diverse perspectives are considered.
Keywords: Environmental; Impact; Assessment; Sustainable; Development